Fenretinide Improves Intestinal Barrier Function and Mitigates Alcohol Liver Disease - Tang, Xiao-Han; Melis, Marta; Mai, Karen; Gudas, Lorraine J.; Trasino, Steven E. (Frontiers in Pharmacology, 2021)
Alcohol liver disease (ALD) is a major cause of liver-related mortality globally, yet there remains an unmet demand for approved ALD drugs. The pathogenesis of ALD involves perturbations to the intestinal barrier and subsequent translocation of bacterial endotoxin that, acting through toll-like receptor 4 (TLR4), promotes hepatic inflammation and progression of ALD. In the present study we investigated the ability of fenretinide (Fen) [N-(4-hydroxyphenyl) retinamide], a synthetic retinoid with known anti-cancer and anti-inflammatory properties, to modulate intestinal permeability and clinical hallmarks of ALD in a mouse model of chronic ethanol (EtOH) exposure. Our results show that EtOH-treated mice had reductions in mRNA and protein expression of intestinal tight junction proteins, including claudin one and occludin, and increases in intestinal permeability and endotoxemia compared to pair-fed mice. Also, EtOH-treated mice had marked increases in hepatic steatosis, liver injury, and expression of pro-inflammatory mediators, including TNF-α, and TLR4-positive macrophages, Kupffer cells, and hepatocytes in the intestines and liver, respectively. In contrast, EtOH + Fen-treated mice were resistant to the effects of EtOH on promoting intestinal permeability and had higher intestinal protein levels of claudin one and occludin. Also, EtOH + Fen-treated mice had significantly lower plasma levels of endotoxin, and reductions in expression of TNF-α and TLR4 positive macrophages, Kupffer cells, and hepatocytes in the intestine and liver. Lastly, we found that EtOH + Fen-treated mice exhibited major reductions in hepatic triglycerides, steatosis, and liver injury compared to EtOH-treated mice. Our findings are the first to demonstrate that Fen possesses anti-ALD properties, potentially through modulation of the intestinal barrier function, endotoxemia, and TLR4-mediated inflammation. These data warrant further pre-clinical investigations of Fen as a potential anti-ALD drug.